Antiviral gene expression in psoriasis. (23rd March 2015) - Raposo, R.A.; Gupta, R.; Abdel‐Mohsen, M.; Dimon, M.; Debbaneh, M.; Jiang, W.; York, V.A.; Leadabrand, K.S.; Brown, G.; Malakouti, M.; Arron, S.; Kuebler, P.J.; et al.
Abstract Background Psoriasis patients have relatively infrequent cutaneous viral infections compared to atopic dermatitis patients. Increased expression of four antiviral proteins (MX1, BST2, ISG15 and OAS2) has been reported in psoriatic skin and genetic studies of psoriasis have identified susceptibility genes in antiviral pathways. Objective To determine if psoriasis is associated with pervasive expression of antiviral genes in skin and blood. Methods We performed RNA sequencing on skin samples of 18 subjects with chronic plaque psoriasis and 16 healthy controls. We examined the expression of a predefined set of 42 antiviral genes, each of which has been shown in previous studies to inhibit viral replication. In parallel, we examined antiviral gene expression in atopic dermatitis, non‐lesional psoriatic skin and psoriatic blood. We performed HIV‐1 infectivity assays in CD4+ peripheral blood T cells from psoriatic and healthy individuals. Results We observed significant overexpression of 16 antiviral genes in lesional psoriatic skin, with a greater than two‐fold increase in ISG15, RSAD2, IRF7, MX2 and TRIM22 (P < 1E‐07). None of these genes was overexpressed in atopic dermatitis skin (P < 0.0001) or non‐lesional psoriatic skin. In contrast to the skin compartment, no differences in antiviral gene expression were detected in the peripheral blood of psoriasis cases compared to healthy controls. CD4+ T cells from both psoriatic and healthy patients supported HIV‐1 infection at a similar rate. Conclusion Our findings highlight psoriasis as an inflammatory disease with cutaneous but not systemic immune activation against viral pathogens.